The Concept of Local Wisdom: Synergy between University and Local Government in the Development of Tourism Villages - Nadi Suprapto; Suliyanah Suliyanah; Utama Alan Deta; Setyo Admoko; Bonda Sisephaputra; Muchamad Arif Al Ardha; Hasan Nuurul Hidaayatullaah; Khoirun Nisa'; Imam Sya'roni (Studies in Philosophy of Science and Education, 2022)
The purpose of this research is to assist villagers in preparing village tourism roadmaps, especially sports tourism, assisting in creating content on social media to promote village local wisdom as well as promote virtual village tourism (virtual tourism). The approach method used is Focus Group Discussion, modeling, workshops, and peer tutoring both in preparing village roadmaps and developing creative content. The research results obtained were upgrading through village potential inventory activities, human resource management, especially knowledge about virtual tourism and sports tourism, and marketing through social media carried out by the team to partners, namely getting a positive response. There has been an increase in the knowledge and understanding of the community in creating social media accounts, determining creative ideas for promotion, and preparing roadmaps for tourism villages (sports tourism and virtual tourism). The development of tourism potential and community empowerment is carried out because there are many potential natural resources (food and tourist objects), human resources, and cultural resources (Bull Racing) to be developed and shared with a wide audience through social media which will later bring benefits and benefits for the local community.